Urinary Fatty Acid Binding Protein 3 Has Prognostic Value in Peripheral Artery Disease - Li, Ben; Zamzam, Abdelrahman; Syed, Muzammil H.; Jahanpour, Niousha; Jain, Shubha; Abdin, Rawand; Qadura, Mohammad (Frontiers in Cardiovascular Medicine, 2022)
Background Despite its significant association with limb loss and death, peripheral artery disease (PAD) remains underdiagnosed and undertreated. The current accepted gold-standard for PAD screening, the ankle brachial index (ABI), is limited by operator dependence, erroneous interpretation, and unreliability in patients with diabetes. Fatty acid binding protein 3 (FABP3) is an intracellular protein that becomes released into circulation and excreted into urine following skeletal muscle injury. We examined the prognostic ability of urinary FABP3 (uFABP3) in predicting adverse PAD-related events. Methods In this prospective case-control study, urine samples were collected from patients with PAD (n = 142) and without PAD (n = 72). The cohort was followed for 2 years. uFABP3 was normalized to urinary creatinine (uCr) (uFABP3/uCr). The primary outcome was major adverse limb event (MALE; composite of vascular intervention [open or endovascular] or major limb amputation). The secondary outcome was worsening PAD status (drop in ABI≥0.15). Cox regression analyses with multivariable adjustment for baseline demographic and clinical variables were performed to assess the prognostic value of uFABP3/uCr with regards to predicting MALE and worsening PAD status. Results Patients with PAD had significantly higher median [IQR] uFABP3/uCr levels (3.46 [2.45–6.90] vs. 2.61 [1.98–4.62], p = 0.001). MALE and worsening PAD status were observed in 21 (10%) and 28 (14%) patients, respectively. uFABP3/uCr predicted MALE and worsening PAD status with adjusted hazard ratios (HR) of 1.28 (1.16–1.41, p = 0.001) and 1.16 (1.02–1.27, p = 0.021), respectively. Patients with high uFABP3/uCr had a lower 2-year freedom from MALE (86 vs. 96%, p = 0.047) and worsening PAD status (78 vs. 99%, p = 0.001). There was good discriminatory ability for uFABP3/uCr in predicting the primary outcome of MALE, with an area under the receiver operating characteristics curve (AUROC) of 0.78. Conclusions Measuring uFABP3/uCr levels in patients with PAD can help identify those at high risk of adverse PAD-related events. This study highlights the prognostic value of uFABP3 in risk-stratifying individuals for further diagnostic vascular evaluation or aggressive medical management.